2011
DOI: 10.1016/j.mcn.2011.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of lipopolysaccharide-induced microglia activation by calcitonin gene related peptide and adrenomedullin

Abstract: Calcitonin gene related peptide (CGRP) and adrenomedullin are potent biologically active peptides that have been proposed to play an important role in vascular and inflammatory diseases. Their function in the central nervous system is still unclear since they have been proposed as either pro-inflammatory or neuroprotective factors. We investigated the effects of the two peptides on astrocytes and microglia, cells of the central nervous system that exert a strong modulatory activity in the neuroinflammatory pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 57 publications
2
44
1
Order By: Relevance
“…In fact, the sensory neurons and their peptides may contribute to the maintenance of tissue integrity by regulating the inflammatory response, as suggested by the results of the current study. Consistent with these findings, researchers have noted that CGRP treatment can inhibit the production of TNF-α and other pro-inflammatory cytokines (Millet et al 2000;Consonni et al 2011). In addition, as one of the prostaglandins, PGI2 can exert anti-inflammatory effects by inhibiting the production of TNF through inhibition of its transcription (Jorres et al 1997).…”
Section: Discussionmentioning
confidence: 64%
“…In fact, the sensory neurons and their peptides may contribute to the maintenance of tissue integrity by regulating the inflammatory response, as suggested by the results of the current study. Consistent with these findings, researchers have noted that CGRP treatment can inhibit the production of TNF-α and other pro-inflammatory cytokines (Millet et al 2000;Consonni et al 2011). In addition, as one of the prostaglandins, PGI2 can exert anti-inflammatory effects by inhibiting the production of TNF through inhibition of its transcription (Jorres et al 1997).…”
Section: Discussionmentioning
confidence: 64%
“…Primary microglia was prepared according to Consonni et al (2011) and a pCDNA3 expression plasmid encoding Venus-RCP was transfected by Lipofectamine 2000 (Life Technologies) following manufacturer's instructions. Quantification of Venus-RCP in the nucleus was performed by IN Cell Analyzer 1000 (GE Lifesciences).…”
Section: Methodsmentioning
confidence: 99%
“…CGRP and adrenomedullin brain-restricted actions have been analyzed in headaches studies, but whether the action is restricted to sensory endings of brain vasculature or brain parenchyma has not yet been defined. We recently showed that both CGRP and adrenomedullin inhibit the secretion of pro-inflammatory mediators from activated microglia (Consonni et al, 2011), and in the current studies we have addressed the role of these peptides in neuroinflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Cytokine concentrations were used according to the literature as to obtain maximal effect on glial cells (see [43] and references therein) [41,44]. In some cases N ω -Nitro-L-arginine methyl ester hydrochloride (L-NAME), an arginine-analog that selectively inhibits iNOS function was administered at different concentrations (0.1, 0.25 and 1 mM) 1 hour before pro-inflammatory stimuli administration and left for the entire duration of the treatment.…”
Section: Methodsmentioning
confidence: 99%